Reciprocity and emotions : arousal, self-reports, and expectations - Gershon Ben-Shakhar; Gary Bornstein; Astrid Hopfensitz; Frans van Winden (Center for Economic Studies and ifo Institute (CESifo), 2004)
Although reciprocity is a key concept in the social sciences, it is still unclear why people engage in costly reciprocation. In this study, physiological and self-report measures were employed to investigate the role of emotions, using the Power-to-Take Game. In this 2-person game, player 1 can claim any part of player 2's resources, and player 2 can react by destroying some (or all) of these resources thus preventing their transfer to player 1. Both physiological and self-report measures were related to destruction decisions and expectations. The pattern of emotional arousal and its correlation with self-reported anger highlights the importance of using both techniques for studying reciprocity.
Keywords: C91; C72; A12; 330; emotions; bargaining; laboratory experiment; expectations; reciprocity; physiological arousal; self-report measures of emotions; Verhandlungstheorie; Gerechtigkeit; Emotion; Experiment